Outcomes of resections that spare vs remove an MRI‐normal hippocampus. (16th October 2020) - Morita‐Sherman, Marcia; Louis, Shreya; Vegh, Deborah; Busch, Robyn M.; Ferguson, Lisa; Bingaman, Justin; Bulacio, Juan; Najm, Imad; Jones, Stephen; Zajichek, Alexander; Hogue, Olivia; Kattan, Michael W.; et al.
Abstract: Objective: To characterize seizure and cognitive outcomes of sparing vs removing an magnetic resonance imaging (MRI)–normal hippocampus in patients with temporal lobe epilepsy. Methods: In this retrospective cohort study, we reviewed clinical, imaging, surgical, and histopathological data on 152 individuals with temporal lobe epilepsy and nonlesional hippocampi categorized into hippocampus‐spared (n = 74) or hippocampus‐resected (n = 78). Extra‐hippocampal lesions were allowed. Pre‐ and postoperative cognitive data were available on 86 patients. Predictors of seizure and cognitive outcomes were identified using Cox‐proportional hazard modeling followed by treatment‐specific model reduction according to Akaike information criterion, and built into an online risk calculator. Results: Seizures recurred in 40% within one postoperative year, and in 63% within six postoperative years. Male gender ( P = .03), longer epilepsy duration ( P < .01), normal MRI ( P = .04), invasive evaluation ( P = .02), and acute postoperative seizures ( P < .01) were associated with a higher risk of recurrence. We found no significant difference in postoperative seizure freedom rates at 5 years between those whose hippocampus was spared and those whose hippocampus was resected ( P = .17). Seizure outcome models built with pre‐ and postoperative data had bootstrap validated concordance indices of 0.65 and 0.72. The dominant hippocampus‐spared group had lower rates of decline in verbal memory (39% vs 70%; P = .03) and naming (41% vs 79%; P = .01) compared to the hippocampus‐resected group. Partial hippocampus sparing had the same risk of verbal memory decline as for complete removal. Significance: Sparing or removing an MRI‐normal hippocampus yielded similar long‐term seizure outcome. A more conservative approach, sparing the hippocampus, only partially shields patients from postoperative cognitive deficits. Risk calculators are provided to facilitate clinical counseling.